Penambahan Wawasan Kompetensi Literasi Sains Melalui Pembelajaran Praktikum Virtual Bagi Guru-guru MGMP Biologi Kabupaten Tanjung Jabung Timur - Kartika, Winda Dwi; Hariyadi, Bambang; Subagyo, Agus; Murni, Pinta; Siburian, Jodion (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Teachers in the regions need training and assistance, especially during the current Covid-19 pandemic. The Biology Subject Teacher Deliberation (MGMP) of Tanjung Jabung Timur Regency in collaboration with the Community Service Team of the Biology Education Study Program, Jambi University seeks to find solutions to several problems faced by teachers as partners by designing virtual practicum training and simple practicum. Service activities are carried out of increasing teacher knowledge regarding scientific literacy competencies in conditions with limited facilities and infrastructure. Through this training activity, it is expected to increase the creativity and innovation of teachers in carrying out practicums. The implementation of the service is designed online through several platforms, namely zoom meeting, WAG and google form. The Devotion Team made learning videos and virtual practicum guides and prepared materials that were distributed to participants via WAG. Furthermore, an online meeting was held through a zoom meeting for the delivery of learning contracts and materials. In general, the implementation of the activities went well. The participants were 20 people, consisting of high school teachers throughout Tanjung Jabung Timur Regency, and the Community Service Team. The activities are carried out through zoom and discussion via WAG. During the implementation via zoom, some participants experienced signal difficulties because the location of their residence/school was quite remote and difficult to access. Furthermore, participants provide weekly reports for invoices from this training activity and discuss actively through WAG.